IMPLEMENTASI PROGRAM MERDEKA BELAJAR UNTUK ANAK USIA DINI MELALUI PROJECT BASED LEARNING - shinta mutiara; Susan Maulani (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Currently, the education system in Indonesia is transforming with the aim of creating human resources that are superior to previous years where the learning approach has changed from teacher-centered learning to student center learning at all levels of education including early childhood education. Various methods are carried out in Early Childhood Education institutions including project-based learning for the implementation of independent learning programs. This study used a qualitative descriptive method using data collection techniques for observation of the learning process and interviews with principals and teachers di sekolah alam pelopor which were carried out over a period of 1 month. Project Based Learning which is also carried out at the pioneer nature school in Bandung, where the implementation is in accordance with the concept and essence of project-based learning itself, children are fully actively involved in planning what activities / products will be produced, preparing the necessary facilities and infrastructure, carry out activities by collaborating with friends, producing a product / work, expressing their own ideas if there are problems that occur to the evaluation process of children discussing. Teachers in sekolah alam pelopor act as facilitators and students as learning centers. Children tend to seem very enthusiastic in activities and all children are active in asking questions, expressing ideas and thinking critically in every problem. Project Based Learning di sekolah alam pelopor menjadi salah satu implementasi program merdeka belajar di lembaga pendidikan anak usia dini.